Utility of a lateral flow immunoassay (LFI) to detect Burkholderia pseudomallei in soil samples - Rongkard, P; Hantrakun, V; Dittrich, S; Srilohasin, P; Amornchai, P; Langla, S; Lim, C; Day, N; AuCoin, D; Wuthiekanun, V; Limmathurotsakul, D (Public Library of Science, 2016)
BACKGROUND: Culture is the gold standard for the detection of environmental B. pseudomallei. In general, soil specimens are cultured in enrichment broth for 2 days, and then the culture broth is streaked on an agar plate and incubated further for 7 days. However, identifying B. pseudomallei on the agar plates among other soil microbes requires expertise and experience. Here, we evaluate a lateral flow immunoassay (LFI) developed to detect B. pseudomallei capsular polysaccharide (CPS) in clinical samples as a tool to detect B. pseudomallei in environmental samples. METHODOLOGY/PRINCIPAL FINDINGS: First, we determined the limit of detection (LOD) of LFI for enrichment broth of the soil specimens. Soil specimens (10 grams/specimen) culture negative for B. pseudomallei were spiked with B. pseudomallei ranging from 10 to 105 CFU, and incubated in 10 ml of enrichment broth in air at 40°C. Then, on day 2, 4 and 7 of incubation, 50 μL of the upper layer of the broth were tested on the LFI, and colony counts to determine quantity of B. pseudomallei in the broth were performed. We found that all five soil specimens inoculated at 10 CFU were negative by LFI on day 2, but four of those five specimens were LFI positive on day 7. The LOD of the LFI was estimated to be roughly 3.8x106 CFU/ml, and culture broth on day 7 was selected as the optimal sample for LFI testing. Second, we evaluated the utility of the LFI by testing 105 soil samples from Northeast Thailand. All samples were also tested by standard culture and quantitative PCR (qPCR) targeting orf2. Of 105 soil samples, 35 (33%) were LFI positive, 25 (24%) were culture positive for B. pseudomallei, and 79 (75%) were qPCR positive. Of 11 LFI positive but standard culture negative specimens, six were confirmed by having the enrichment broth on day 7 culture positive for B. pseudomallei, and an additional three by qPCR. The LFI had 97% (30/31) sensitivity to detect soil specimens culture positive for B. pseudomallei. CONCLUSIONS/SIGNIFICANCE: The LFI can be used to detect B. pseudomallei in soil samples, and to select which samples should be sent to reference laboratories or proceed further for bacterial isolation and confirmation. This could considerably decrease laboratory workload and assist the development of a risk map for melioidosis in resource-limited settings.